2016
DOI: 10.2337/db16-0917
|View full text |Cite
|
Sign up to set email alerts
|

Brain GLUT4 Knockout Mice Have Impaired Glucose Tolerance, Decreased Insulin Sensitivity, and Impaired Hypoglycemic Counterregulation

Abstract: GLUT4 in muscle and adipose tissue is important in maintaining glucose homeostasis. However, the role of insulin-responsive GLUT4 in the central nervous system has not been well characterized. To assess its importance, a selective knockout of brain GLUT4 (BG4KO) was generated by crossing Nestin-Cre mice with GLUT4-floxed mice. BG4KO mice had a 99% reduction in GLUT4 protein expression throughout the brain. Despite normal feeding and fasting glycemia, BG4KO mice were glucose intolerant, demonstrated hepatic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 44 publications
5
60
0
4
Order By: Relevance
“…Key features of these glucose‐sensing neurones and glia are the expression of the low affinity, high capacity GLUT2 and glucokinase (GK), both of which are expressed in the brain with high levels in the hypothalamus With kinetics characterised by a k m around 10 mmol L ‐1 , V m around 20 mmol L ‐1 and GK not being inhibited by its end product glucose‐6‐phosphate, GLUT2 and GK are ideally suited to glucose‐sensing: facilitating glucose transport and metabolism aligned to shifts in blood and CSF glucose levels. More recently, a key role for GLUT4 in CNS glucose‐sensing and glucose homeostasis has also been suggested . Age‐ and HFD‐dependent changes in any aspect of these interacting pathways could contribute to central glucose intolerance and ultimately contribute further to peripheral glucose intolerance and diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Key features of these glucose‐sensing neurones and glia are the expression of the low affinity, high capacity GLUT2 and glucokinase (GK), both of which are expressed in the brain with high levels in the hypothalamus With kinetics characterised by a k m around 10 mmol L ‐1 , V m around 20 mmol L ‐1 and GK not being inhibited by its end product glucose‐6‐phosphate, GLUT2 and GK are ideally suited to glucose‐sensing: facilitating glucose transport and metabolism aligned to shifts in blood and CSF glucose levels. More recently, a key role for GLUT4 in CNS glucose‐sensing and glucose homeostasis has also been suggested . Age‐ and HFD‐dependent changes in any aspect of these interacting pathways could contribute to central glucose intolerance and ultimately contribute further to peripheral glucose intolerance and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Because the BBB is considered the primary rate limiting factor determining glucose entry into the CNS and glucose transport across the BBB is via the GLUT1 glucose transporter protein, changes in GLUT1 expression and/or function could underpin age‐ and HFD‐induced changes in central glucose tolerance. GLUT1 is fundamental to maintaining BBB integrity, capillary networks and blood flow and a reduced expression of GLUT1 is a contributing factor to neurodegeneration and abnormal neuronal function . Reduced GLUT1 expression at the level of the BBB is a feature of Alzheimer's disease and recent studies showed that HFD‐induced a transient decrease in GLUT1 expression, although GLUT1 expression was recovered, despite the maintained HFD, in a myeloid‐cell‐derived vascular endothelial growth factor (VEGF)‐dependent manner .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, GLUT4 is also expressed in the hypothalamus 81 , a key area for metabolic control. Deletion of GLUT4 from the CNS in mice results in impaired glucose sensing and tolerance 82 , which might be due in part to an absence of GLUT4 in the hypothalamus.…”
Section: Insulin and The Brainmentioning
confidence: 99%
“…Mice from two N ‐ethyl‐ N ‐nitrosourea (ENU) lines show abnormal, low amplitude voluntary wheel‐running activity patterns. Circadian activity patterns are double plotted for ease of visualization, with each horizontal line representing 48 hours and successive days plotted along the Y‐axis. Wheel revolutions are depicted as black marks on the horizontal lines.…”
Section: Resultsmentioning
confidence: 99%